Newfoundland Country Music Pioneers. Jimmy Linegar - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. School of Continuing Studies and Extension, 1978)
Jimmy Linegar, who started performing country music on the radio at age 15, discusses this early career with host Neil Rosenberg. Linegar plays and sings with Newfoundland musical group Crooked Stovepipe.